Local and global magnetic properties of Zn1-xCoxO and Mn-doped GaAs thin films - Iwamoto, W.; Urbano, R. R.; Pagliuso, P. G.; Rettori, C.; Samanta, K.; Bhattacharya, P.; Katiyar, R. S.; Silva, José Humberto Dias da [UNESP]; Pereira, Andre; Azevedo, G. de M.; Oseroff, S. B. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
Amorphous and crystalline thin films of Mn-doped(0.5%-10%) GaAs and crystalline thin films of Zn1-xCoxO(x = 3%-20%) were investigated by means of magnetic susceptibility and electron spin resonance (ESR). For the Mn-doped GaAs samples, our results show the absence of ferromagnetic ordering for the amorphous films in the 300 > T > 2 K temperature range, in contrast to the ferromagnetism found in crystalline films for T-C < 110 K. A single ESR line with a temperature independent g-value (g similar to 2) is observed for the amorphous films, and the behavior of this ESR linewidth depends on the level of crystallinity of the film. For the Mn-doped GaAs crystalline films, only a ferromagnetic mode is observed for T < TC when the film is ferromagnetic. Turning now the Zn1-xCoxO films, ferromagnetic loops were observed at room temperature for these films. The magnetization data show an increasing of the saturation magnetization M. as a function of x reaching a maximum value for x approximate to 10%. ESR experiments at T = 300 K in the same films show a strong anisotropic ferromagnetic mode (FMR) for x = 0.10.
Keywords: dilute ferromagnetic semiconductors; electron spin resonance; magnetization curves